A new yellow-flowered Chiloschista (Orchidaceae: Aeridinae) from Thailand - Dalström, Stig (Universidad de Costa Rica, 2020)
A new species of Chiloschista Lindl. from western Thailand is described and illustrated with a line drawing and photographs. It is compared with the sympatric C. parishii Seidenf., from which it differs in having larger flowers, which are 11–12 mm across versus 8–10 mm across for C. parishii. The new species also distinctly differs in having widely spreading rostellum lobes and a viscidium that is as broad as the length of the stipe, as opposed to downward directed rostellum lobes and a viscidium that is distinctly narrower than the length of the stipe for C. parishii. The same distinguishing features separate the new species from the similarly colored C. trudelii Seidenf., which has inward-directed rostellum lobes and a viscidium that is distinctly narrower than the length of the stipe. Key words: Epidendroideae, new Chiloschista, Thailand orchid flora, Vandeae